2021
DOI: 10.3390/microorganisms9091948
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Alteration after Reboxetine Administration in Type-1 Diabetic Rats

Abstract: Antidepressants are drugs commonly used in clinical settings. However, there are very limited studies on the effects of these drugs on the gut microbiota. Herein, we evaluated the effect of reboxetine (RBX), a selective norepinephrine (noradrenaline) reuptake inhibitor (NRI), on gut microbiota in both diabetic and non-diabetic rats. This is the first report of relation between reboxetine use and the gut microbiota to our knowledge. In this study, type-1 diabetes induced by using streptozotocin (STZ) and RBX wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…Lactobacillus genus represents a common probiotic, but this protective effect may depend on the presence of other intestinal bacteria and work together in a complementary manner ( 49 ). Most other studies have reported that Lactobacillus was found in higher abundance in control groups than in diabetic groups ( 50 , 51 ). But here, the abundance of Lactobacillus being significantly higher in the DCM group than in the CON group.…”
Section: Discussionmentioning
confidence: 82%
“…Lactobacillus genus represents a common probiotic, but this protective effect may depend on the presence of other intestinal bacteria and work together in a complementary manner ( 49 ). Most other studies have reported that Lactobacillus was found in higher abundance in control groups than in diabetic groups ( 50 , 51 ). But here, the abundance of Lactobacillus being significantly higher in the DCM group than in the CON group.…”
Section: Discussionmentioning
confidence: 82%
“…However, RBX treatment significantly affected beta diversity in healthy and diabetic rates compared to the control. Relative taxa analysis reveals that RBX treatment reduced Firmicutes but increased Bacteroides, and Proteobacteria phyla (Aydin et al, 2021). In terms of families, Prevotellaceae increased, but Lactobacillaceae and Clostridiaceae decreased.…”
Section: Analysis Part 2: Antidepressantsmentioning
confidence: 95%
“…In terms of families, Prevotellaceae increased, but Lactobacillaceae and Clostridiaceae decreased. Random forest analysis, this is a technique that assigns OTU's, and is a form of metagenomic sequencing that uses the 16sribosomal RNA to identify species in a particular sample, and fecal samples were analyzed in this study (Aydin et al, 2021). There was a total of 3782 OTU's identified even though there was not any significant difference on the species level there was a significant difference in diversity within the microbiome (Aydin et al, 2021).…”
Section: Analysis Part 2: Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reboksetin duygudurum, dikkat, öğrenme ve bellek fonksiyonlarında kritik rol oynadığı bilinen bir nörotransmitter olan noradrenalin'in santral nörotransmisyonunu artırarak gerek emosyon gerekse kognisyon üzerine olumlu etkiler gösterdiği bilinen antidepresan bir ilaçtır [18][19][20][21][22]. Literatürde reboksetin'in diyabetik deneklerde plazma glukoz seviyeleri, nöropatik ağrı parametreleri ve barsak mikrobiyomu üzerine etkilerinin araştırıldığı bazı çalışmalar bulunmakla birlikte, bu antidepresanın diyabete bağlı olarak gelişen depresyon, anksiyete ve öğrenme/bellek zayıflıkları üzerine etkileri daha önce araştırılmamıştır [23][24][25]. Bu nedenle bu çalışmada, reboksetin'in, deney hayvanlarında diyabet ile indüklenen emosyonel ve bilişsel bozukluklar üzerine farmakolojik etkilerinin araştırılması amaçlanmıştır.…”
Section: Introductionunclassified